STUDY AND DESIGN OF HIGH FREQUENCY AC-DC CONVERTER CIRCUIT IN WIRELESS CHARGING APPLICATIONS OF ELECTRIC VEHICLE - CHOIRUL ABDILLAH - NIM. 18014036 , DANANG
Inductive power transfer systems in wireless charging applications generally consist of a primary part (AC-AC converter), a magnetic coupling transfer circuit, and a secondary circuit (AC-DC converter). IPT system is run at a high frequency of 50,000 Hz which is the resonant frequency of the transfer circuit. This study discusses the secondary section which basically consists of a series of rectifiers, buck converters, and controls used in charging the battery. This series will be modeled with PSIM and Matlab Simulink software. The type of rectfier used is an uncontrolled full bridge and a buck converter is designed using two MOSFETs. The process of controlling as a battery charging regulator is done in buck converter circuit. Battery charge simulation is used 14V fixed voltage mode where control is performed on buck converter. The current control is done on the AC-AC converter section for output not to exceed 10A. With this control, we will see the charging regulator output to the battery voltage change or the State of Charge (SOC) change of battery along with its efficiency. The output of each simulation will then be compared and analyzed according to the specifications and theories.